Evaluation of the retinal vasculature of patients with branch retinal vein occlusion using optical coherence tomography angiography - Moura,Bárbara de Carvalho Freire Santos (2020)
ABSTRACT Purpose: To evaluate vascular density in superficial and deep capillary plexuses of the retina, measured using optical coherence tomography angiography in patients with branch retinal vein occlusion. Affected eyes were compared with the contralateral eye of the same patient and both were compared with normal eyes. Methods: A cross-sectional study including 16 previously untreated patients with branch retinal vein occlusion. Patients with poor quality examinations, bilateral disease, high refractive error, or any other retinal or choroidal disease were excluded. A total of 31 patients without eye disease were also selected as a comparison group. All participants underwent five optical coherence tomography angiographies, and only those with at least two good quality examinations were selected. The Kruskal-Wallis, Wilcoxon signed-rank, and Mann-Whitney U tests were used for the statistical analysis. Results: Vascular density was lower in affected eyes compared with contralateral eyes: whole density (p=0.020 for capillary plexuses superficial; p=0.049 for deep capillary plexuses) and parafoveal density (p=0.020 for capillary plexuses superficial; p=0.011 for deep capillary plexuses). Vascular density was also lower in affected eyes compared with normal eyes: whole density (p<0.001 for capillary plexuses superficial and deep) and parafoveal density (p<0.001 for capillary plexuses superficial and deep). Whole density (p=0.001 for capillary plexuses superficial and deep) and parafoveal density (p=0.001 for capillary plexuses superficial; p<0.001 for deep capillary plexuses) were both lower in the contralateral eyes compared with normal eyes. Following adjustment for arterial hypertension, this difference was no longer observed. Conclusions: Vascular density in capillary plexuses and deep capillary plexuses was lower in the eyes affected by branch retinal vein occlusion. Furthermore, the lower vascular density noted in the contralateral eyes indicates that changes most likely occurred in these eyes prior to the appearance of any clinically detectable alterations, reflecting the early signs of hypertensive retinopathy.